Trade‐offs in transitions between indigenous and commercial fishing sectors: the Torres Strait tropical rock lobster fishery. (December 2016) - Hutton, T.; van Putten, E.I.; Pascoe, S.D.; Deng, R.A.; Plagányi, É.E.; Dennis, D.
Abstract: A bio‐economic model was developed to evaluate aspects of proposed quota‐based constraints vs the current effort control regulations for the tropical rock lobster, Panulirus ornatus, Fabricius, fishery in the Torres Strait (Australia/Papua New Guinea). The analysis integrates across biological, economic and social considerations. Model performance indicators have been chosen to reflect higher level policy objectives. The model simulation results indicate important trade‐offs. There is lower overall fleet total profit (across all the subfleets), lower fishery total value added and lower total employment if the fishery is quota‐constrained. This is due to an assumed rationalisation driven by incentives and current utilisation of capacity. The simulated re‐allocation of quota from the commercial non‐indigenous fleet allowing for greater potential indigenous fisher participation results in predicted increases in indigenous employment and would meet social objectives; however, due to limited capacity in the indigenous fleet, the simulated predicted lower catches led to lower total fishery profits and decreased total fishery value added within the supply chain. Investment in capacity could potentially offset this result.